100 children of UMPSA staff receive school uniform donations - Nor Salwana, Mohammad Idris (UMPSA, 2024)
GAMBANG, 28 February 2024 - A total of 100 children of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) staff received donations of school necessities from the UMPSA Foundation, reflecting the university's concern in alleviating the schooling expenses of staff members in need.